NILAI-NILAI PENDIDIKAN DALAM KITAB SIRAJ AL THALIBIN KARYA SYEKH IHSAN BIN DAHLAN - Fatkhul Wahab (Pascasarjana Institut Agama Islam Al-Qolam, 2023)
Education aims to (1) develop morally good and correct behavior, (2) cultivate autonomous reflection skills, (3) internalize moral values and norms in facing concrete life situations, (4) adopt universal principles and life values as a foundation for moral development in decision-making, and (5) make righteous, moral, and wise decisions. The purpose of this research is to understand the concept of education contained in the book